THE STUDY OF EPIC POEM “GARIB-ASHIQ” - Jiemuratova Gulistan Koshkinbaevna (Research Focus International Scientific Journal, 2025)
The thesis tells about the origin of the poem and its distribution to the world. This thesis raises and explores questions concerning the popularity of the saga in Central Asia from ancient times. Compares various versions recorded by famous bakshi, poets and different ideas of the scientists about background of the saga. Under this single term “Garib-ashiq”, the plot line of the versions of the story, the motive, the image, and the origin of the story show influence on the formation of the national culture.